2020
DOI: 10.1155/2020/4652439
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lower Urinary Tract Dysfunction Impact on Quality of Life in Multiple Sclerosis Patients: Russian Translation and Validation of SF-Qualiveen

Abstract: The Short Form Qualiveen (SF-Qualiveen) is an 8-item version of the Qualiveen questionnaire used to evaluate the impact of urinary symptoms on the quality of life in patients with urological dysfunction due to neurological disorders. The questionnaire was never available in the Russian language before. The study is aimed at providing the translation, cultural adaptation, and validation of a Russian version of the SF-Qualiveen for the use in patients with multiple sclerosis (MS). Materials and Methods. The orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
(38 reference statements)
4
7
0
Order By: Relevance
“…The Turkish version of SF-Qualiveen demonstrated good internal consistency (Cronbach's alpha >0.8), similar to previous validation studies of the SF-Qualiveen. [8][9][10][11] In our study, the domains "bother with limitations" and "feeling" showed good internal consistency and the domains "frequency of limitations" and "fears" showed weak internal consistency. Although similar results are reported in the Dutch version, internal consistency was found to be high in all domains of the scale in the Polish and Russian studies.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…The Turkish version of SF-Qualiveen demonstrated good internal consistency (Cronbach's alpha >0.8), similar to previous validation studies of the SF-Qualiveen. [8][9][10][11] In our study, the domains "bother with limitations" and "feeling" showed good internal consistency and the domains "frequency of limitations" and "fears" showed weak internal consistency. Although similar results are reported in the Dutch version, internal consistency was found to be high in all domains of the scale in the Polish and Russian studies.…”
Section: Discussionmentioning
confidence: 45%
“…9 The test-retest reliability of the SF-Qualiveen was found to be excellent in our study, as previously reported in the literature. [8][9][10][11] We believe that the reason for the high test-retest results was related to the scale's concise and coherent structure. The patients' low disability levels also contributed to this results.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations